Fundamentals of project management - Heagney, Joseph (American Management Association, 2016)
Boasting sales of more than 200,000 copies, Fundamentals of Project Management has helped generations of project managers navigate the ins and outs of every aspect of this complex discipline. But much has changed in recent years. Fully updated in accordance with the latest version of the Project Management Body of Knowledge (PMBOK®), the fifth edition of this classic text remains the perfect introduction to the subject.